Students’ Experience of Family Counseling Role-Play with Developmental Considerations - Emily Horton; Crystal Hughes; Priscilla R Prasath; Jessica Lloyd-Hazlett (Teaching and Supervision in Counseling, 2022)
A need exists to explore student experiences with pedagogical approaches, particularly those commonly used in counselor education such as role-play. Nine counselors-in-training (CITs) who participated in a semester-long family counseling role-play shared their experiences with the pedagogical approach. Through semi-structured interview protocol, we explored CITs’ lived experience and meaning-making with the learning strategy. Existing literature denotes that cognitive complexity influences how CITs make sense of their experiences. As such, cognitive complexity scores, rooted in Perry’s intellectual development model, are provided for each participant. Data were analyzed using transcendental phenomenology, which resulted in three superordinate themes: impact of class structure, increased confidence, and gained meta-awareness. Findings suggest the value of role-play as a pedagogical strategy for counselors-in-training of various cognitive developmental levels.
Keywords: role-play; cognitive development; family counseling